CMOS based thermal detector for processor - Lee, Che Yang; Mat Jubadi, Warsuzarina (2020)
This project proposed a design of low power CMOS-based thermal detector which can detect the temperature of processor such as in Central Processing Unit. By re-designing temperature detector circuit using CMOS technology, the reduction in power consumption and area size of the thermal detector can be obtained. In this paper, the design of thermal detector consists of temperature sensing core, amplifier, and Analog to Digital Converter (ADC), respectively. The sensor was designed using 0.13 μm CMOS technology and operates by sensing the temperature of processor and produced a digital output value. The temperature detection range was setup between 0 °C to 80 °C with 10 °C resolution. The temperature detector was capable to show temperature readings in binary value. It consumed an average power of 558.2 μW and a space occupancy of 0.0118 mm².